Pengaruh Likuiditas, Total Asset Turnover, Debt to Equity Ratio dan Perputaran Persedian terhadap Profitabilitas Perusahaan Manufaktur - Ferica Ferica; Annisa Nauli; Cindy Couwinata; Sukhenny Sukhenny (COSTING : Journal of Economic, Business and Accounting, 2020)
Profitability in a company aims to assess the company's expertise in generating profits and the company's ability to pay debts to creditors. This study aims to determine the effect of Liquidity (QR), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Inventory Turnover on profitability. This type of research is quantitative descriptive with secondary data, sample selection using purposive sampling, and testing methods using multiple linear regression analysis. The population in this study amounted to 155 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. Based on the results of the study note that simultaneous Liquidity (QR), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Inventory Turnover have positive and significant effects. Partially, only Liquidity (QR) and Total Assets Turnover (TATO) have a positive and significant effect on profitability while Debt to Equity Ratio (DER), and Inventory Turnover have no significant effect on profitability. Keywords : Liquidity, Total Assets Turnover, Debt to Equity Ratio, and Inventory Turnover